The Belgian Accent of the Finnish Avant-Garde: Alfred William Finch’s Art in Finland - Klyushina, Elena V. (Actual Problems of Theory and History of Art, 2020)
The article explores the Finnish stage of the creative work of Alfred William Finch, the Belgian painter, engraver, and master of applied arts. The author sees her task in establishing the degree of influence that the artist could potentially have on the representatives of Finnish avant-garde art, as well as in identifying the direct results of his creative, pedagogical, and curatorial activities in Finland. The article provides a brief historiographic review and discusses the problem of exhibiting the master’s works in European museum collections. A special emphasis has been made on the achievements of the “Iris” ceramic factory, which was opened and operated jointly with Luis Sparre in 1897. The ceramics created in the city of Porvoo is one of the foundations forthe renovation of decorative and applied arts in Southern Finland. Even more attention has been paid to the role of Finch in the organization of the Franco-Belgian exhibition at the Athenaeum in 1904. It is emphasized that in order to achieve the best result, Finch used his broad European connections to get the Finnish public acquainted with the latest achievements of European art. The article also gives a brief description of the activities of Finch as a teacher, his assistance in organizing foreign internships for Finnish artists in London, Weimar, etc.
Keywords: Alfred William Finch; Porvoo; Iris; Louis Sparre; Art Nouveau; ceramics; Finnish art; Society XX; Belgium